An anatomy of entrepreneurial pursuits in relation to poverty. Issue 1 (1st January 2020) - Cumming, Douglas; Johan, Sofia; Uzuegbunam, Ikenna
ABSTRACT: This study examines the causal relationships between inequality, poverty and entrepreneurship. We hypothesize that income inequality influences entrepreneurial activity, and entrepreneurial activity alleviates absolute poverty. Findings from longitudinal analyses of a dataset from all 50 US states over an 18-year period provide robust support for these hypotheses. Furthermore, the results suggest that antipoverty public policy aimed at encouraging work (i.e. Earned income tax credit, EITC) can be detrimental to entrepreneurial activity. These findings underscore the importance of linking public policy efforts aimed at poverty alleviation with those aimed at encouraging additional entrepreneurship.